Who Stays and Who Leaves? Father Accessibility Across Children’s First 5 Years - Shannon, Jacqueline D. (2009)
OBJECTIVE: This longitudinal investigation examines whether fathers’ prenatal involvement (e.g., attending doctor appointments and discussing pregnancy with mother) and residence status at infant’s birth predict the first time a father becomes inaccessible to his child (defined as seeing child fewer than a few times per month) at six developmental time points in children’s first 5 years. DESIGN: Data were gathered from 2,160 ethnically diverse mothers (i.e., European American, African American, and Latin American) who participated in the National Early Head Start Research and Evaluation Project. Survival analysis was used to predict the timing of father inaccessibility based on interviews. RESULTS: By prekindergarten, fathers’ residence at birth and prenatal involvement decreased their risk of being inaccessible to their children for the first time by 71% and 47%, respectively, after adjusting for all other variables in the model. Residence at birth was a stronger predictor of the timing of father inaccessibility than was prenatal involvement for European American and Latin American fathers; for African American fathers, prenatal involvement was a stronger predictor of the timing of father inaccessibility than nonresidential status at birth. Nearly 65% of fathers who were engaged in both prenatal activities remained consistently accessible to their child through child age of 63 months, whereas nearly 50% of fathers who were not prenatally involved were already inaccessible by the time infants were 3 months. CONCLUSION: These findings have implications for early intervention programs aimed at strengthening the role of fathers in their families from the prenatal period.